Assessment of Dolichandrone falcata Seem. Leaves for Anti-cancer Potential in Experimental Animal Models - Kapse, Sachin N.; Bhamare, Vaibhav G.; Amrutkar, Rakesh D.; Patil, Rahul N.; Patil, Vinod R.; Talele, Gokul S. (Indian Journal of Pharmaceutical Education and Research, 2024)
Background: Mammary cancer is the most common type of cancer and the leading cause of cancer-related death in women. Despite of numerous therapeutic options, cancer remains associated with high mortality. Traditional herb medicine has been found effective with minimal or no side effects. Materials and Methods: The leaves of Dolichandrone falcata Seem. (Bignoniaceae family) contains chrysin-7-rutinoside, flavanoids which possess Anti-cancer potential. The extract obtained from Soxhlet extraction process is then assessed against the chemical carcinogen (7,12-Dimethyl benzene anthracene) induced mammary carcinoma in rats. Results and Conclusion: The dose dependent study and statistical comparison with the help of graph pad prism, version 8.03 by one way ANOVA followed by Dunnett’s multiple comparison test has revealed that the significant reduction (p<0.05) is observed in the mammary tumor volume of the group treated with the extract and hence the Anti-cancer Potential of Dolichandrone falcata Seem. is justified.
Keywords: Dolichandrone falcata; Anti-cancer; Flavonoids; Chemical carcinogen; Rats